Identification and Prioritization of Business Risks of Poultry Production Units - Maliheh Sheibani Nougabi; Alireza Karbasi; Hosein Mohammadi (مجله اقتصاد و توسعه کشاورزی, 2024)
IntroductionToday, the businesses of the poultry industry are facing many challenges, because this industry has to manage a number of unique processes, methods and risks at the same time. Therefore, identifying the business risks of poultry production units can play an effective role in reducing the level of vulnerability of these businesses. Considering the need to increase the productivity of the poultry industry, one of the basic solutions is to identify the risk and measure the existing risks of this industry. Risk identification and quantification can reduce costs for industry stakeholders, and risk reduction leads to better production planning. In this regard, this study identifies the business risks of poultry production units in Khorasan Razavi province. Materials and MethodsThis study is applied as purpose and descriptive survey in terms of nature and method. This research is based on mixed research, qualitatively and quantitatively. The statistical population is poultry industry experts, 18 of whom were investigated by snowball sampling method as the research sample. This study proposes a new Delphi technique that uses the features of traditional Delphi techniques and the Fuzzy Delphi method. The proposed new Delphi technique is based on the integration of pentagonal fuzzy sets and the Delphi technique. Results and DiscussionThe results of the modified pentagonal Fuzzy Delphi method showed that five main risks and 36 secondary risks out of 58 identified risks are part of the business risks of poultry production units. Identified business risks of poultry production units, in order of priority, include inputs price fluctuations, command pricing, exchange rate fluctuations, sanctions, chicken price fluctuations, delay in accessing inputs, fluctuations in the purchase price of day-old chickens, fluctuations in drug and vaccine prices, imported inputs, lack of government support in the matter of production, fluctuations in subsidies to inputs, lack of animal inputs, import of poultry products, Promulgation of various instructions, poultry diseases, lack of liquidity of poultry farmers, bankruptcy of poultry farmers, fluctuations in current costs, losses, lack of medicine and vaccines, lack of expansion of poultry business, lack of confidence of poultry farmers in the government, fluctuations in profitability, investment, seasonal fluctuations in egg demand, dependence of poultry farmers on Special suppliers, supply of day-old chicks, lack of energy, exclusivity of the livestock and poultry feed supply system, egg price fluctuations, seasonal fluctuations in chicken production, seasonal fluctuations in chicken demand, weakness in providing working capital facilities to poultry farmers, lack of skilled human resources in time Appropriate, lack of technical knowledge of advanced technologies and lack of variety of poultry food ingredients. ConclusionThe business of poultry production units is facing various challenges and risks, and due to the many risks of this industry, production in this industry is facing problems and it is not possible to plan for it, and production will be disrupted in the future. Therefore, in this research, an effort was made to fully identify the business risks of poultry production units. In order to complete and finalize the business risks of poultry production units, the pentagonal Fuzzy Delphi method was used. In this regard, a questionnaire was prepared that included two parts. The first part is about the survey and information about the background of the respondents, and the second part includes the ranking of 54 identified risks. Fuzzy Delphi method in this study was done in two rounds and based on the opinion of experts, 4 more risks were added to the total of 54 risks, and finally 58 risks were analyzed using Fuzzy Delphi method. In Fuzzy Delphi, the selection of risk components among all the components that were identified in the research literature was based on the accepted threshold criterion. The results of the second round of modified pentagonal Fuzzy Delphi showed that there are 36 important sub-risks in the sector of production, market, financial, institutional and personal business risks of poultry production units. Considering the price fluctuations of livestock inputs and exchange rate fluctuations, it is suggested to allocate currency and control it by government policies in order to reduce mentioned fluctuations, or move towards diversifying poultry feed ingredients and formulating new poultry feed rations. Also, in order to avoid fluctuations in the price of chicken or eggs, it is suggested to make the distribution network smarter to prevent these fluctuations. In the poultry market, it is better to set a fair price for each kilogram of chicken according to the production costs of poultry farmers, or not to interfere with the government in the market and allow the government to set the price based on the supply and demand mechanism.